Thermal and conductivity studies of composite polymer blend electrolytes based on poly(ethylene oxide) and epoxidized natural rubber / Fatin Harun - Harun, Fatin (Institute of Graduate Studies, UiTM, 2018)
In this study, immiscible blends of poly(ethylene oxide) (PEO) and epoxidized natural rubber with 50 mol% epoxide content (ENR-50) added with lithium perchlorate (LiC104) and nano-sized titanium dioxide (Ti02) were studied. To have a systematic comparison, a series of systems of PEO/LiC104, PEO/Ti02, PEO/LiC104/Ti02, ENR-50/ LiC104, ENR-50/TiO2, ENR-50/LiClO4/TiO2, PEO/ENR-50, PEO/ ENR-50/LiClO4 and PEO/ENR-50/LiClO4/TiO2 were prepared via solution casting method. The thermal properties, conductivity, intermolecular interaction, morphologies, crystalline structures and rheological behavior were studied accordingly with greater emphasis on the relationship between thermal properties and conductivity behaviour. From impedance spectroscopy analysis…